Distributed Open-Domain Conversational Understanding Framework With Domain Independent Extractors - Li, Qi; Tur, Gokhan; Hakkani-Tür, Dilek; Li, Xiang; Paek, Tim; Gunawardana, Asela; Quirk, Chris (IEEE Spoken Language Technology Workshop, 2014)
Traditional spoken dialog systems are usually based on a centralized architecture, in which the number of domains is predefined, and the provider is fixed for a given domain and intent. The spoken language understanding (SLU) component is responsible for detecting domain and intents, and filling domain-specific slots. It is expensive and time-consuming in this architecture to add new and/or competing domains, intents, or providers. The rapid growth of service providers in the mobile computing market calls for an extensible dialog system framework. This paper presents a distributed dialog infrastructure where each domain or provider is agnostic of others, and processes the user utterances independently using their own knowledge or models, so that a new domain and new provider can be easily incorporated in. In addition, to facilitate each service provider building their own SLU models or algorithms, we introduce a new component, extractors, to provide intermediate semantic annotations such as entity mention tags, which can be plugged in arbitrarily as well. Each service provider can then rapidly develop their SLU parser with minimum efforts by providing some example sentences with intents and slots if needed. Our preliminary experimental results demonstrate the power of this new framework compared to a centralized architecture.